Meghdoot—A Mobile App to Access Location-Specific Weather-Based Agro-Advisories Pan India - Dhulipala, Ram K.; Gogumalla, Pranuthi; Karuturi, Rao; Palanisamy, Ramaraj; Smith, Andrew; Nagaraji, Satish; Rao, Suryachandra A.; Vishnoi, Lata; Singh, Kamalesh K.; Bhan, Subhash C.; Whitbread, Anthony M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Timely agricultural advisories to farmers can enhance their decision-making and reduce production risk under challenging weather conditions. To enhance access to relevant climate information services in India, a mobile application called Meghdoot was designed to deliver weather information and crop-specific advisories, as a joint initiative of the India Meteorological Department (IMD), Indian Institution for Tropical Meteorology (IITM), Indian Council for Agricultural Research (ICAR) and the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT). Building on IMD’s District Agrometeorological Advisory Service (DAAS) which issues crop-specific weather-based agro-advisories twice a week for all districts in India, the Meghdoot app makes available observed weather recordings, forecasts, and warnings generated by IMD and IITM. This working paper describes the concept design, the framework and a preliminary user analysis of the Meghdoot mobile application. Meghdoot mobile app is available on Google Play (Google Play Store) as well as Apple App Store. Since its inception more than two years ago, Meghdoot has received a good response with 200,000+ downloads/installs and an average rating of 3.3/5.0 by 863 app users (as of July 26, 2021) on Google Play(Google Play Store).